Phytochemical Analysis and Prostate Cancer Cytotoxicity of Iraqi Apium graveolens: A GC-MS Approach - Mais A. Abood; Abdul-Jalil, Thukaa; Ibrahem, Nabaa (Iraqi Journal of Pharmaceutical Sciences, 2025)
Apium graveolens has been utilized for a multitude of purposes due to its diverse pharmacological characteristics. On the other hand, little is known about how the fatty acids (saturated and unsaturated) terpenes and steroids found in Iraqi Apium graveolens affect the human cancer cells. The purpose of this study was to examine the effects of Iraqi Apium graveolens petroleum ether extract on the human prostate cancer cell line (PC3). Subsidiary extraction and phytochemical analysis by GC/MS were performed.The dry and fresh aerial parts (leaves and stem) of Apium graveolens were extracted using a Soxhlet device with 70 % ethanol, then fractionated with petroleum ether. Then Gas Chromatography System was used to identify the bioactive components, and The MTT assay was performed in human prostate cancer cell line (PC3) that was treated with different concentrations of the petroleum ether extract of both the fresh and dried parts (250, 500, and 1000μg/ml) and the results were compared to docetaxel as a control drug after 24,48, and 72 hrs of treatment, and cell viability was evaluated. The fresh part of the of Iraqi Apium graveolens was richer with important saturated fatty acids, steroids and terpenes more than the dry part. Furthermore, the fresh part showed a considerable cytotoxic activity in the human prostate cancer cell line (PC3), which is a concentration and time dependent effect; The half-maximum inhibitory concentration (IC50) values were reduced over time from 1549, 183.6, to 26.45μg/ml, and the cytotoxicity was increased with a remarkable reduction in the cancer cell viability. The fresh part of the petroleum ether fraction of Iraqi Apium graveolens has potential anticancer activity in prostate cancer more than the dried part. This result opens the minds to the fresh plant era and challenges the traditional belief that the dry plants produce better results than the fresh ones.